Does Long Term Residence Mitigate Intercultural Communication Challenges? Insights from Migrant Workers in Taiwan - Sofa Priyandayani Nasution; Siti Isma Sari Lubis; Armita Novriana Rambe (Talenta Publisher, 2026)
This qualitative study investigates the extent to which long-term residence influences intercultural communication challenges among Indonesian migrant workers in Taiwan. Data were collected through semi-structured interviews with 11 participants who have resided in Taiwan for more than 10 years, focusing on their experiences in both workplace and social contexts. The findings indicate that prolonged residence does not necessarily reduce intercultural communication difficulties; instead, these challenges evolve over time. Persistent barriers remain in areas such as religious practices, language proficiency, food-related customs, and nonverbal communication, whereas relationships with employers tend to improve due to increased trust and familiarity. Participants also demonstrate various adaptive strategies, including seeking clarification and negotiating meaning, engaging in cultural learning, and participating in local cultural activities, reflecting their active role in managing cultural differences. Overall, intercultural communication competence is better conceptualized as a dynamic and continuous process shaped by interaction, lived experience, and structural factors, rather than length of stay alone.